Contesting the place of protest in migrant caravans. Issue 2 (2nd July 2020) - Franz, Margaret
ABSTRACT: Restrictions on assembly, all of which disproportionately target Black, Indigenous, and People of Color, demonstrate that the freedom to assemble depends on state-defined temporal, behavioral, and spatial boundaries of political practice. This essay analyzes how the migrant caravans organized by Pueblo Sin Fronteras (PSF) push against the state-derived boundaries on assembly. Specifically, it focuses on two tactics deployed by the caravans: (1) using the term caravan and caravana to describe border crossing, and (2) media practices that turned undocumented border crossing into border refusal. These tactics contested the nation-state sovereignty required to mark its jurisdiction, and thus, to decide on the correct place and form of politics. In the end, the essay argues that the caravan expanded what it means to freely assemble by turning undocumented migration into protest. Communication scholars should pay attention to this expansion because it illuminates alternate ways of being political that push against the legacy of nation-state sovereignty and colonization.